ANALISIS KEMAMPUAN PEDAGOGICAL CONTENT KNOWLEDGE (PCK) CALON GURU SD MELALUI PEMBELAJARAN IPA SD - Niken Yuni Astiti; Jody Setya Hermawan; Rizki Maulita; Kinanti Dyah Nur Islami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the Pedagogical Content Knowledge (PCK) abilities of prospective elementary school teachers in the context of science learning. PCK competence is a key factor for preservice teachers in designing and implementing contextual, systematic, and meaningful science instruction. This study is motivated by the importance of synergy between content knowledge and pedagogy in framing science learning that aligns with the characteristics of elementary students, as mandated in the Merdeka Curriculum and national education policies. A descriptive quantitative approach was employed, with data collected through questionnaires developed based on five core components of PCK. The research subjects were fifth-semester students of the Elementary Teacher Education (PGSD) program at the University of Lampung who were enrolled in a science learning course. The sample was selected using purposive sampling, and the data were analyzed using descriptive statistical techniques. The findings are expected to provide a concrete overview of the PCK mastery level of PGSD students in science learning, which may serve as a basis for curriculum development, training design, and instructional strategies in teacher education. This study also supports the strengthening of preservice teachers’ professionalism in responding to the demands of 21st-century education.